An analysis of the descriptors of acute myocardial infarction used by South Africans when calling for an ambulance from a National Emergency Call Centre - Buma, Chloe Ashton (Department of Surgery, 2020)
Introduction Acute Myocardial Infarction (AMI) is a time sensitive emergency. In resource limited settings such as South Africa, prompt identification and management of these patients in the pre-hospital setting may minimise the negative consequences of an overburdened emergency medical and hospital service. Expedited care thus, in part, relies on the dispatch of appropriate pre-hospital medical providers by emergency medical dispatchers. Identification of these patients in the call centre is challenging due to a highly diverse South African society, with multiple languages, cultures, and levels of education. The aim of this study was therefore, to describe the terms used by members of the South African public when calling for an ambulance for patients suffering an AMI. Methodology In this qualitative study, we performed content analysis to identify keywords and phrases that callers used to describe patients who were experiencing an AMI. Using the patient report form number of randomly selected paramedic- diagnosed AMI cases, original voice recordings between the caller and call centre operators at the time of the emergency were extracted and transcribed verbatim. Descriptors of AMI were identified, coded and categorised using content analysis, and quantified. Results Of the 50 randomly selected calls analysed, 5 were not conducted in English. The descriptors (meaning units) used by callers were and found to fall into three categories; Pain: Thorax, No pain: Thorax and Ill- health. The code that occurred most often was no pain, heart related (n=16; 23.2%), followed by the code describing pain in the chest (n=15; 21.7%). Conclusion South African callers use a consistent set of descriptors when requesting an ambulance for a patient experiencing an AMI. The most common of these are non- pain descriptors related to the heart (“heart attack”). These descriptors may ultimately be used in developing validated algorithms to assist dispatch decisions. In this way, we hope to expedite the correct level of care to these time- critical patients and prevent the dispatching of resource limited advanced life support paramedics to inappropriate cases.